Temporal aspects of the pathophysiology of human ulcer disease - Tarquini, B; Vener, K J (Chronobiology international, 1987)
In this paper, a peptic ulcer is considered from the perspective that it is representative of a heterogeneous group of multifactorial determined or influenced disorders having a common pathomorphologic expression. This heterogeneity involves pathophysiological attributes, including both functional (including secretory and motility events and their respective driving mechanisms) and morphologic alterations that relate to mucosal resistance. Patients with duodenal ulcer (DU) have been observed to exhibit alterations, in comparison to normal subjects, in the circadian rhythm characteristics of several gastrointestinal functions. Prominent among these are altered amplitudes of several circadian-organized gastric variables, such as intragastric pH, gastrin, pepsinogen and gastric mitotic index. With respect to any given variable, a reduced group amplitude (a measure of one-half the peak-trough difference of a 24-hr rhythm) could signify an increased dispersion of acrophases (the location of the peak of a circadian rhythm along the 24-hr time scale) reflecting interindividual variation in synchronization schedules, sleep-wake patterns, or chronobiologic alterations. A reduced interindividual amplitude further supports the concept of the heterogeneity of peptic disease. A decrease in the intraindividual amplitude of certain gastric rhythms implies an altered temporal pattern over the 24 hr. This is consistent with the hypothesis of a decrease in the amount of time available for recovery of a given function or set of integrated functions, and hence, increased susceptibility to mucosal injury. Normal high-amplitude variation in gastrointestinal functioning over the 24 hr appears to be required for natural restoration of the gut.